2006
DOI: 10.1007/s10616-006-9025-4
|View full text |Cite
|
Sign up to set email alerts
|

Insulin secretion dynamics of free and alginate-encapsulated insulinoma cells

Abstract: This study investigates the effect of alginate/poly-L: -lysine/alginate (APA) encapsulation on the insulin secretion dynamics exhibited by an encapsulated cell system. Experiments were performed with the aid of a home-built perfusion apparatus providing a 1 min temporal resolution. Insulin profiles were measured from: (i) murine insulinoma betaTC3 cells encapsulated in calcium alginate/poly-L: -lysine/alginate (APA) beads generated with high guluronic (G) or high mannuoric (M) content alginate, and (ii) murine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The data show that APA‐encapsulated βTC‐tet cells cultured in the absence of TC displayed a glucose consumption increase due to continuous cellular proliferation, while APA beads cultured in the presence of TC maintained their initial metabolic activity for the experiment duration because cell proliferation was suppressed. These dynamics of regulated and unregulated growth of βTC‐tet cells are consistent with previously published data (34, 35). These data also demonstrate that labeling these model tissue‐engineered constructs in either the extracellular alginate matrix or the cells did not affect the gross metabolic activity of encapsulated cells.…”
Section: Resultssupporting
confidence: 92%
“…The data show that APA‐encapsulated βTC‐tet cells cultured in the absence of TC displayed a glucose consumption increase due to continuous cellular proliferation, while APA beads cultured in the presence of TC maintained their initial metabolic activity for the experiment duration because cell proliferation was suppressed. These dynamics of regulated and unregulated growth of βTC‐tet cells are consistent with previously published data (34, 35). These data also demonstrate that labeling these model tissue‐engineered constructs in either the extracellular alginate matrix or the cells did not affect the gross metabolic activity of encapsulated cells.…”
Section: Resultssupporting
confidence: 92%
“…The beads used in these insulin secretion experiments were not returned to the main culture. The 30 min secretion period was sufficient to capture the stimulated secretory response (Cheng et al 2006). Secretion rates were calculated in pmol insulin per hour and per 10 8 cells.…”
Section: 0 Materials and Methodsmentioning
confidence: 99%
“…Encapsulation has been intensively tested as a perspective tool for immunoisolation of transplanted pancreatic islets [55]. It was shown that encapsulation in alginate beads does not affect the insulin secretion profile in vitro [55,56].…”
Section: +mentioning
confidence: 99%